Agrarian Systems Diagnosis and Cooperatives' support to a divergent typology of farmers. The Case of the Riet River Irrigation Scheme - Anseeuw, Ward, 1974- (University of Pretoria, 2015)
Dissertation (MScAgric)--University of Pretoria, 2014.